Cancer Nanotechnology - de Sousa, Ângela Maria Almeida; Soares, Christiane Pienna [UNESP]; Chorilli, Marlus [UNESP] (Springer Nature, 2022)
Cancer nanotechnology is a growing, emerging area of cross-disciplinary research that aims to develop efficient, specific and noninvasive approaches to restore the health and well-being of all cancer patients through more effective diagnosis and treatment. This new volume serves as a fundamental guide to cutting-edge topics in cancer nanotechnology, including advances in therapy, the use of nanoparticles and nanomaterials, future directions for nanocarriers in cancer therapy, and the application of DNA and RNA nanovaccines. Organized into four sections, the volume presents an overview of research and innovation in the emerging field of nanotechnology as a powerful tool in the diagnosis, imaging and treatment of cancer. International experts author chapters addressing targets of cancer therapy, materials for cancer nanotechnology, strategies for cancer therapy using nanotechnology, and innovative nanotechnologies for cancer diagnosis and treatment. The volume will be useful for a broad audience, including cross-disciplinary researchers, trainees, health professionals, and experts in industry.
Keywords: cancer development; cancer phototheragnostic; cancer prognosis; cancer therapies; DNA nanovaccines; epigenetics; gene silencing; immunotherapy; lipid nanocarriers; metastatic cancer; mitochondrial disorders; Monoclonal antibodies; nano-fabrication technologies; Nanobiopharmaceuticals; nanostructures; nanovaccines; peptides; proteins; RNA nanovaccines